Manajemen Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Dalam Ketuntasan Hasil Belajar Kelas Xi di SMA Negeri 2 Polewali - Ridwan; Abd. Wahid; Laziman Laziman; Munawarah Munawarah; Muhammad Aslam Ahmad (Universitas Islam DDI A.G.H Abdurrahman Ambo Dalle, 2025)
This study aims to describe and analyze the implementation of Islamic Religious Education and Character Education learning management in improving the learning outcomes of grade XI students at SMA Negeri 2 Polewali, Polewali Mandar Regency. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Educators implement learning management systematically through the stages of planning, organizing, implementing, and evaluating which include cognitive, affective, and psychomotor aspects. The learning process integrates various methods, such as lectures, discussions, questions and answers, assignments, and application of materials, which effectively encourage the achievement of learning completion. Most students obtained grades in the